PENERAPAN KONSEP DAN PRINSIP GOOD CORPORATE GOVERNANCE PADA PENERAPAN KONSEP DAN PRINSIP GGOD CORPORATE GOVERNANCE PADA PT. KIW (Persero) - Eni Puji Estuti; Cahyani Tunggal Sari; Siti Khayatun (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2022)
Good corporate governance is believed to be one of the main keys of the company in the long term and has an impact on the profits achieved by the company, therefore the company must prepare a statement on the implementation of GCG in its annual report. The implementation of GCG that is not maximized by economic stakeholders both from the government and the private sector will result in an economy that does not run well. The main objective of implementing GCG in SOEs is to maximize the performance of state companies so that they are able to be competitive and have a positive impact on all stakeholders. This research takes a case study at PT. KIW (Persero) as one of the SOEs, where the incident is more implementing GCG. In this study using a quantitative descriptive approach. The results of the analysis show that the implementation of GCG concepts and principles has been carried out well although there needs to be an improvement in information governance technology which is not currently owned by PT, KIW (Persero).